Body Esteem: The Relationship Between Father Involvement, Nurturant Father and Young Adults’ Body Image Perception - Noor Syuhadah Binti Hairul Anuar (Universiti Sains Islam Malaysia, 2024)
Matric: 3221007 (FKP)